The Hunga Tonga‐Hunga Ha'apai Hydration of the Stratosphere. Issue 13 (1st July 2022) - Millán, L.; Santee, M. L.; Lambert, A.; Livesey, N. J.; Werner, F.; Schwartz, M. J.; Pumphrey, H. C.; Manney, G. L.; Wang, Y.; Su, H.; Wu, L.; Read, W. G.; et al.
Abstract: Following the 15 January 2022 Hunga Tonga‐Hunga Ha'apai eruption, several trace gases measured by the Aura Microwave Limb Sounder (MLS) displayed anomalous stratospheric values. Trajectories and radiance simulations confirm that the H2 O, SO2, and HCl enhancements were injected by the eruption. In comparison with those from previous eruptions, the SO2 and HCl mass injections were unexceptional, although they reached higher altitudes. In contrast, the H2 O injection was unprecedented in both magnitude (far exceeding any previous values in the 17‐year MLS record) and altitude (penetrating into the mesosphere). We estimate the mass of H2 O injected into the stratosphere to be 146 ± 5 Tg, or ∼10% of the stratospheric burden. It may take several years for the H2 O plume to dissipate. This eruption could impact climate not through surface cooling due to sulfate aerosols, but rather through surface warming due to the radiative forcing from the excess stratospheric H2 O. Plain Language Summary: The violent Hunga Tonga‐Hunga Ha'apai eruption on 15 January 2022 not only injected ash into the stratosphere but also large amounts of water vapor, breaking all records for direct injection of water vapor, by a volcano or otherwise, in the satellite era. This is not surprising since the Hunga Tonga‐Hunga Ha'apai caldera was formerly situated 150 m below sea level. The massive blast injected water vapor up to altitudes as high as 53 km. Using measurements from the Microwave Limb Sounder on NASA's Aura satellite, we estimate that the excess water vapor is equivalent to around 10% of the amount of water vapor typically residing in the stratosphere. Unlike previous strong eruptions, this event may not cool the surface, but rather it could potentially warm the surface due to the excess water vapor. Key Points: Following the Hunga Tonga‐Hunga Ha'apai eruption, the Aura Microwave Limb Sounder measured enhancements of stratospheric H2 O, SO2, and HCl The mass of SO2 and HCl injected is comparable to that from prior eruptions, whereas the magnitude of the H2 O injection is unprecedented Excess stratospheric H2 O will persist for years, could affect stratospheric chemistry and dynamics, and may lead to surface warming